2017
DOI: 10.1111/dom.13164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an energy‐restricted low‐carbohydrate, high unsaturated fat/low saturated fat diet versus a high‐carbohydrate, low‐fat diet in type 2 diabetes: A 2‐year randomized clinical trial

Abstract: Both diets achieved comparable weight loss and HbA1c reductions. The LC sustained greater reductions in diabetes medication requirements, and in improvements in diurnal blood glucose stability and blood lipid profile, with no adverse renal effects, suggesting greater optimization of T2D management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
213
3
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(249 citation statements)
references
References 58 publications
(96 reference statements)
7
213
3
10
Order By: Relevance
“…Of these, 10/21 purposefully reduced or minimized the intake of saturated fat. Four studies reported their fat type prescriptions in a quantifiable manner ranging from 8% to 10%, 20% to 49%, and 10% to 13% TEI for saturated, monounsaturated, polyunsaturated fat, respectively . One study was a liquid diet in which the fat was derived from monounsaturated‐enriched sunflower oil .…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 10/21 purposefully reduced or minimized the intake of saturated fat. Four studies reported their fat type prescriptions in a quantifiable manner ranging from 8% to 10%, 20% to 49%, and 10% to 13% TEI for saturated, monounsaturated, polyunsaturated fat, respectively . One study was a liquid diet in which the fat was derived from monounsaturated‐enriched sunflower oil .…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from 30 trials and 10 follow‐up studies shows that a low‐carbohydrate diet is an effective dietary approach for addressing dyslipidaemia. More than half of the studies that reported triglyceride levels found a significant improvement from baseline with a low‐carbohydrate diet; eight also showed superiority over a control diet . Similarly, the evidence consistently showed significant improvements in HDL cholesterol with a low‐carbohydrate diet, with 10 studies finding a significant increase over control diet .…”
Section: Resultsmentioning
confidence: 96%
“…All 12 single‐arm and non‐randomized trials found that a low‐carbohydrate diet significantly improved glycaemic control from baseline to end of study; the two studies that made between‐group comparisons found the low‐carbohydrate diet superior to the control diet . We identified eight longer‐term studies (1‐3 years' duration), of which five found significant glycaemic benefit sustained with a low‐carbohydrate diet; these include two 2‐year trials and a 3‐year trial . Another longer trial also found sustained improvement in glycaemic control at 44 weeks .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar confusion surrounds carbohydrate diets, despite the importance of carbohydrate in glycaemic control. A recent clinical trial found similar reductions in weight and HbA 1c in patients with T2D who were placed on either low or high carbohydrate diets, though an increased reduction in diabetes medication was also seen in the low carbohydrate group . Generally though, ‘there is a lack of long‐term studies on the effect of carbohydrate diets and a lack of clarity on what constitutes the definition of low carbohydrate,’ said Dr Mellor.…”
Section: Foods For Glycaemic Control and Cvd Preventionmentioning
confidence: 99%